The Error Types and Teaching Design of Indonesian Learners' Chinese Adverbs of Degree "FEICHANG/SHIFEN" - Juniana Juniana; Mei Rianto Chandra; Qian Kun (Jurnal Sinestesia, 2023)
Mandarin "feichang/shifen" is often used by students who learn foreign languages. However, several misunderstandings can still be found in their usage, especially when translated into Indonesian. For example, "feichang" can only be combined with adjective + noun + noun, but nor for "shifen" and Indonesia "sangat." This research mainly investigates the errors of Indonesian learners in the Chinese proficiency adverbs "feichang" and "shifen" and then propose a more effective teaching design. This research uses a qualitative method, classifying the types of errors and causes of errors using Chinese shifen/feichang on 60 Indonesian students. It is found that the error is mainly because the student's grasp of the Chinese "feichang/shifen" syntax is relatively low and not specific enough. Besides that, the meaning between feichang/shifen and the Indonesian language "sangat" is relatively close. When using meanings containing informal words, "feichang" is more acceptable than "shifen." Finally, the "feichang/shifen" teaching design is proposed through the induction of errors, hoping to provide a more effective "feichang/shifen" learning strategy for Indonesian learners of Mandarin.